The Impact Of Employment Status: Self-Employment And Wage-Employment On Mental Health - Marwa Sari; Putu Geniki Lavinia Natih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study analyzes the impact of employment status on mental health by comparing self-employed and wage-employed individuals in Indonesia. Using longitudinal data from the Indonesia Family Life Survey (IFLS) waves 4 and 5, this study applies a fixed effects model to explore this relationship while accounting for various demographic and socioeconomic controls. The findings reveal that self-employed individuals have higher mental health scores, indicating poorer mental health compared to wage-employed individuals. However, this effect becomes insignificant after including control variables in the model. Job transition analysis indicates that individuals transitioning from self-employment to wage-employment tend to have higher mental health scores, while those remaining in wage employment exhibit a lower risk of mental health issues. Heterogeneity analysis reveals that self-employed women are more vulnerable to mental health issues compared to men, while individuals with disabilities demonstrate better mental health in self-employment than in wage employment.